Pemanfaatan Teknologi Digital sebagai Media Pembelajaran Interaktif untuk Siswa Sekolah Dasar - Siti Aisyah; Ayu Fitriya Ramadani; Anggita Eka Wulandari; Choli Astutik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
In this digital era, various information can be accessed through digital media. For example, in the world of education, digital technology is used as a means to support the learning process in schools so that learning is more innovative and creative so that students are interested in always learning. This study aims to ensure that learning in schools, especially elementary schools, can learn and utilize digital technology properly so that they can create interactive learning and leave behind the tradition of using outdated methods or media. The process of compiling this research article uses a literature review method, which aims to analyze and synthesize information from several literature sources that are in accordance with the topic being discussed. The results of the literature review state that by utilizing digital technology, students can easily increase their interest and learning outcomes so that an interactive learning atmosphere can be easily created.